2012
DOI: 10.1167/12.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Fixation-related potentials in visual search: A combined EEG and eye tracking study

Abstract: We report a study of concurrent eye movements and electroencephalographic (EEG) recordings while subjects freely explored a search array looking for hidden targets. We describe a sequence of fixation-event related potentials (fERPs) that unfolds during ∼ 400 ms following each fixation. This sequence highly resembles the event-related responses in a replay experiment, in which subjects kept fixation while a sequence of images occurred around the fovea simulating the spatial and temporal patterns during the free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
145
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(154 citation statements)
references
References 77 publications
8
145
0
1
Order By: Relevance
“…Despite the existence of a large amount of studies describing EFRPs, almost all of them are performed in well-controlled laboratory studies using simple stimuli [11]. More important, even those studies using more natural stimuli typically employ static images, avoid gaze shifts or instructed subjects to fixate during long periods (>300ms) [8], [12], [13]. This has allowed to identify discriminat late EFRP components [8], even at a single subject level [11].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the existence of a large amount of studies describing EFRPs, almost all of them are performed in well-controlled laboratory studies using simple stimuli [11]. More important, even those studies using more natural stimuli typically employ static images, avoid gaze shifts or instructed subjects to fixate during long periods (>300ms) [8], [12], [13]. This has allowed to identify discriminat late EFRP components [8], even at a single subject level [11].…”
Section: Resultsmentioning
confidence: 99%
“…The symbols were chosen because they are geometrically and saliently equivalent. The surrounding # signs are there to create a crowding effect and force the foveating in the center of the board [8]. The boards are evenly spaced by 30 m, and placed randomly on either side of the street.…”
Section: A Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Another route of improving the model would be to add information from brain signals. It has been shown that by relating EEG traces to eye fixations, it is possible to distinguish above chance whether an observer is looking at a looked-for target (which in this case would be a geological model error) or not (Brouwer et al, 2013(Brouwer et al, , 2014Kamienkowski et al, 2012).…”
Section: Resultsmentioning
confidence: 99%